LANGUAGE LEARNING INTELLIGENCE MANAGEMENT INDONESIA IN EARLY CHILDREN: Case Study Learning Play at TK Kemala Bhayangkari 43 and TK Melati, Jatinangor District, Sumedang Regency - Lisnawati, Lisnawati; Asep Saepudin; Riandiani, Ani (JIV-Jurnal Ilmiah Visi, 2022)
This study is to analyse and describe the planning, organizing, implementing, evaluating, constraints and solutions to learn Indonesian language intellgence in kindergarten. This research uses descriptive method and qualitative approach. Research subjects were the principal, teachers, students and parents / school committee. Data collection techniques using interviews, observations, and documentations. The results of the study are: What the teacher of kindergarten Kemala Bhayangkari 43 and teacher of kindergarten Melati jatinangor Sub-district Sumedang District have done has referred to the management of learning, which caused the teacher’s role in the implementation of Indonesian language intelligence learning to increase, although not significant yet.